Corporate governance practices in listed banks: impact on risk management and resulting financial performance - Quaresma, A.; Pereira, R.; Dias, A. (Journal of Business and Economics, 2014)
This research aims to analyze the relation between the quality of corporate governance practices and the financial performance of international listed banks. In order to meet this goal the variables related to company returns – IL/GL; NL/TA; ROA; ROE and Tier 1 – were associated with the following standards of corporate governance: independence of the board of directors (INDBD); independence of the president of the board of directors (INDPR); size of the board of directors (SZBD); voting power concentration (VPC) and the company`s shareholder independence indicator (BvDep). For the composition of the sample we selected listed banks in several European, American, and Japanese stock markets from the period between 2006 and 2009. Results show a significant relation between best corporate governance practices and financial performance of studied banks. This research confirms results attained in previous works but also provides evidence on previously unexplored relations namely between BvDep and IL/GL and NL/TA variables.